Babinski-Nageotte Syndrome Diagnosed in Postpartum Period. (16th February 2016) - Oruç, Serdar; Demirbaş, Hayri; Güzel, Abdullah; Beker Acay, Mehtap; Yaman, Mehmet
Abstract : Babinski-Nageotte Syndrome (BNS) is one of the brainstem syndromes characterized by muscle weakness in the opposite half of the body with classic Wallenberg findings. According to our literature survey, only a few cases have been reported and none of them was in the postpartum period. We report a case of a typical BNS in a postpartum woman with an ischemic lesion in the medulla oblongata shown on magnetic resonance imaging.